Enhanced wheat yield and flag leaf physiology in saline-alkali soils using modified straw water-retaining agent - Min Yang; Cexun Ji; Kui Chao; Pengfei Zhu; Xiaoqing Yuan; Zenghui Hao; Xiulin Wang; Yan Shi (Agricultural Water Management)
The application of water-retaining agent is one of the hot spots in current agricultural production. In this study, crop straw was modified as one of the raw materials of water-retaining agent to make modified straw water-retaining agent. The effects of modified straw water-retaining agent on wheat photosynthetic and antioxidant characteristics, nutrient accumulation after anthesis and yield were explored. Two-year experiment was conducted, and five treatments were set up: CK (no water-retaining agent), T1 (18 kg·ha−1 modified straw water-retaining agent), T2 (36 kg·ha−1 modified straw water-retaining agent), T3 (54 kg·ha−1 modified straw water-retaining agent), T4 (36 kg·ha−1 commercial water-retaining agent). The results showed that the application of water-retaining agent could increase the chlorophyll content and improve the photosynthetic characteristics of wheat flag leaves, and the application of water-retaining agent was beneficial to increase the activities of Superoxide Dismutase (SOD), Peroxidase (POD) and Ascorbate Peroxidase (APX) and reduce the content of Malondialdehyde (MDA) in wheat flag leaves. Correlation analysis showed that there was a significant correlation between photosynthesis and antioxidant system. The accumulation of nitrogen, phosphorus and potassium in stems, leaves and spikes of T1-T4 was higher or significantly higher than that of CK. The overall yield of the two years was T2 > T4 > T3 > T1 > CK, and compared with CK, T2 and T4 increased significantly by 13.3 %-16.5 % and 9.1 %-12.9 %, respectively. The results of this study can provide theoretical and practical basis for the application of modified straw water-retaining agents in field production.